Inhibition of CYR61-S100A4 Axis Limits Breast Cancer Invasion - Hellinger, Johanna W.; Hüchel, Silke; Goetz, Lena; Bauerschmitz, Gerd; Emons, Günter; Gründker, Carsten (Frontiers in Oncology, 2019)
Background and Objective Matricellular proteins modulate the micro environment of tumors and are recognized to contribute to tumor cell invasion and dissemination. The cysteine-rich angiogenic inducer 61 (CYR61) is upregulated in mesenchymal transformed and invasive breast cancer cells. CYR61 correlates with poor prognosis of breast cancer patients. The signaling mechanism that causes invasive properties of cancer cells regarding to epithelial-mesenchymal transition (EMT) needs further research. In this study, we investigated the signaling mechanism, which is responsible for reduced cell invasion after suppression of CYR61 in mesenchymal transformed breast cancer cells and in triple negative breast cancer cells. Methods We addressed this issue by generating a mesenchymal transformed breast cancer cell line using prolonged mammosphere cultivation. Western blotting and quantitative PCR were used to analyze gene expression alterations. Transient gene silencing was conducted using RNA interference. Proliferation was assessed using AlamarBlue assay. Invasiveness was analyzed using 2D and 3D invasion assays. Immune-histochemical analysis of patient tissue samples was performed to examine the prognostic value of CYR61 expression. Results In this study, we investigated whether CYR61 could be used as therapeutic target and prognostic marker for invasive breast cancer. We discovered an interaction of CYR61 with metastasis-associated protein S100A4. Suppression of CYR61 by RNA interference reduced the expression of S100A4 dependent on ERK1/2 activity regulation. Non-invasive breast cancer cells became invasive due to extracellular CYR61 supplement. Immune-histochemical analysis of 239 patient tissue samples revealed a correlation of higher CYR61 and S100A4 expression with invasive breast cancer and metastasis. Conclusion Our data suggest that suppression of CYR61 impedes the formation of an invasive cancer cell phenotype by reducing ERK1/2 phosphorylation thereby suppressing S100A4. These findings identify mechanisms by which CYR61 suppresses cell invasion and suggest it to be a potential therapeutic target and prognostic marker for invasive breast cancer and metastasis.